Applicability of PRF- platelet-rich fibrin in Dentistry and it’s benefits - Carvalho, Nathane Araujo de (2021)
Providing a quick healing of soft tissue and hard tissue became the greatest goal of surgeons in general, this search started the studies of autologous bioactive surgical additives such as: adhesive fibrin, platelet concentrate rich in plasma and fibrin. Platelet-rich fibrin-PRF was produced in France and is a second-generation platelet concentrate that, due to its properties, provided satisfactory results applied to dentistry, allowing for excellent healing and repair of surgical lesions, aiding in tissue regeneration. It is a 100% autologous safe biomaterial, quick to acquire, more economical, without contraindication, product of the centrifugation of the patient's natural venous blood. Today, much research has been done reporting the use of PRF as a clot and PRF membranes. It is generally applied in oral surgeries for bone augmentation, maxillary sinus elevation, in periodontics, acting in the correction of intraosseous defects and gingival recession, it can also be used for regeneration in open apex, regenerative pulpotomies and periapical surgeries. The present work is a qualitative literature review that aims to carry out a study planning to deepen the knowledge about the application of PRF-Fibrina Rica in platelets. The searches were carried out through selective research of articles, monographs and theses found in electronic databases such as: Pubmed, Scielo and Academic Google with the objective of describing the growth factors present in the PRF, detailing the applicability of the PRF in procedures dental clinics and report the benefits and advantages of PRF over PRP.